2003
DOI: 10.1086/345915
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Absorption and Emission Abundance Analyses of Nebulae: Ion Emission Densities for IC 418

Abstract: ABSTRACT. Recent analyses of nebular spectra have resulted in discrepant abundances from CNO forbidden and recombination lines. We consider independent methods of determining ion abundances for emission nebulae, comparing ion emission measures with column densities derived from resonance absorption lines viewed against the central star continuum. Separate analyses of the nebular emission lines and the stellar UV absorption lines yield independent abundances for ions, and their ratio can be expressed in terms o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The astrophysical importance lies in the fact that there are large discrepancies in abundances of several nebular elements, including C, N, O, S, Fe, and Ni, derived from recombination lines, as opposed to collisionally excited lines [6][7][8]. The present study on O II is also aimed at a possible resolution of this outstanding problem.…”
Section: Introductionmentioning
confidence: 99%
“…The astrophysical importance lies in the fact that there are large discrepancies in abundances of several nebular elements, including C, N, O, S, Fe, and Ni, derived from recombination lines, as opposed to collisionally excited lines [6][7][8]. The present study on O II is also aimed at a possible resolution of this outstanding problem.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that neutral gas is plentifully abundant within the ionized regions. This conjecture was supported by Williams et al (2003), who compared absorption-and emission-line spectra of IC 418 and found evidence that absorbing gas may be present. If we enhance the [O i] emissivity in the inner regions by a factor of ∼1.5, an excellent match between the predicted profile and observed one is achieved, as shown the Fig.…”
Section: Emission Line Profiles Of Ic 418mentioning
confidence: 77%
“…More work is still in progress along these lines by various groups like the IRON Project, the FERRUM Project at Lund University, and the group at the University of Queen's Belfast. At this point it is worth mentioning the work of Williams et al (2003) who compared the abundance ratio Fe + /Ni + in IC 418 as obtained from UV resonant absorption lines, Fe ii λ1260.5 and Ni ii λ1317.2, as opposed to the determination from optical forbidden lines in emission. They get a large discrepancy between Fe + /Ni + >25 from absorption lines and Fe + /Ni + =5 from emission lines.…”
Section: The Iron-peak Elementsmentioning
confidence: 99%